2017
DOI: 10.1128/aem.03133-16
|View full text |Cite
|
Sign up to set email alerts
|

Ketoacylsynthase Domains of a Polyunsaturated Fatty Acid Synthase in Thraustochytrium sp. Strain ATCC 26185 Can Effectively Function as Stand-Alone Enzymes in Escherichia coli

Abstract: sp. strain ATCC 26185 accumulates a high level of docosahexaenoic acid (DHA), a nutritionally important ω-3 very-long-chain polyunsaturated fatty acid (VLCPUFA) synthesized primarily by polyunsaturated fatty acid (PUFA) synthase, a type I polyketide synthase-like megaenzyme. The PUFA synthase in this species comprises three large subunits, each with multiple catalytic domains. It was hypothesized that among these domains, ketoacylsynthase (KS) domains might be critical for catalyzing the condensation of specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…However, the exact molecular mechanism of the PUFA synthase for intricately positioning multiple double bonds in VLCPUFAs has not been fully elucidated. There is evidence that KS and DH domains of a PUFA synthase play key roles in the biosynthesis of VLCPUFAs where DH domains catalyse the introduction of double bonds and KS domains are responsible for retaining the double bonds (Xie et al ., 2017, 2018; Hayashi et al ., 2019a; Hayashi et al ., 2019b). The PUFA synthase in Thraustochytrium possesses two different types of DH domains.…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact molecular mechanism of the PUFA synthase for intricately positioning multiple double bonds in VLCPUFAs has not been fully elucidated. There is evidence that KS and DH domains of a PUFA synthase play key roles in the biosynthesis of VLCPUFAs where DH domains catalyse the introduction of double bonds and KS domains are responsible for retaining the double bonds (Xie et al ., 2017, 2018; Hayashi et al ., 2019a; Hayashi et al ., 2019b). The PUFA synthase in Thraustochytrium possesses two different types of DH domains.…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact functions of these domains in the biosynthesis of these fatty acids are not well characterized. Our previous study indicated that a dissected KS domain from Subunit-B of the PUFA synthase from Thraustochytrium could complement the temperature-sensitive phenotype of E. coli β-ketoacyl-ACP synthase I ( FabB) mutant and enhance the total fatty acid production in a wild-type E. coli strain [17]. In the present study, this domain was further functionally analyzed in A. thaliana .…”
Section: Discussionmentioning
confidence: 86%
“…FAMEs were extracted with 2 mL of hexane and 1 mL of 0.9% NaCl. The total fatty acid profiles and quantity were analyzed on an Agilent 7890A system installed with a DB-23 column (30 m, 0.25 mm, 0.25 µm) [13, 17].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PUFA synthase from Thraustochytrium comprises three large subunits, each with multiple catalytic domains. All these domains are predicted on the presence of characteristic catalytic motifs in the primary sequence, and the exact functions of most of them remain to be determined except for ketoacyl synthase and dehydratase domains of PUFA synthases [ 16 , 17 , 18 , 19 , 20 ]. The purpose of this study was to functionally analyze an acyltransferase (AT)-like domain from Subunit-B of a PUFA synthase in Thraustochytrium through complementation test, site-directed mutagenesis and in vitro assays in E. coli .…”
Section: Introductionmentioning
confidence: 99%